Efektivitas Kebijakan Dana Primer Koperasi Polisi (PRIMKOPPOL) Terhadap Manajemen Keuangan Dalam Meningkatkan Kinerja Koperasi Di Polda Sumatra Utara - Urfa, Mursalati (Journal of Computer Science and Information System(JCoInS), 2024)
Cooperative is a form of organization established by a group of people with the aim to meet the needs and improve the welfare of its members. In cooperatives, membership is open to anyone who has common interests and is willing to actively participate in cooperative activities. In line with the times, the role of cooperatives has developed into a people's economic rally that has a strong business network and competitiveness. The goal is to anticipate future opportunities and challenges. Cooperatives have developed their civilization with purposeful steps, while maintaining a cooperative identity, as well as being able to adapt to other economic practices. Cooperative PRIMKOPPOL acts as the initiator of the development of the economic potential of the people in a particular region. This cooperative aims to improve the welfare of its members by involving them in mutually beneficial economic activities. PRIMKOPPOL seeks to create an inclusive and democratic environment, where every member has equal rights and participates in decision-making. The cooperative also encourages the promotion of Justice, togetherness, and sustainable economic growth. By conducting initiatives and activities in accordance with cooperative principles. To run this program or activity, a team with adequate competencies and skills is needed. Quality human resources will be a key factor in the success of this program. By having the appropriate abilities, expertise, and skills, the team will be able to face challenges and carry out tasks effectively.